Ethacridine inhibits SARS-CoV-2 by inactivating viral particles. - Xiaoquan Li; Peter V Lidsky; Yinghong Xiao; Chien-Ting Wu; Miguel Garcia-Knight; Junjiao Yang; Tsuguhisa Nakayama; Jayakar V Nayak; Peter K Jackson; Raul Andino; Xiaokun Shu (PLoS Pathogens)
The respiratory disease COVID-19 is caused by the coronavirus SARS-CoV-2. Here we report the discovery of ethacridine as a potent drug against SARS-CoV-2 (EC50 ~ 0.08 μM). Ethacridine was identified via high-throughput screening of an FDA-approved drug library in living cells using a fluorescence assay. Plaque assays, RT-PCR and immunofluorescence imaging at various stages of viral infection demonstrate that the main mode of action of ethacridine is through inactivation of viral particles, preventing their binding to the host cells. Consistently, ethacridine is effective in various cell types, including primary human nasal epithelial cells that are cultured in an air-liquid interface. Taken together, our work identifies a promising, potent, and new use of the old drug via a distinct mode of action for inhibiting SARS-CoV-2.